TEACHERS’ PROFILES AFTER THE IMPLEMENTATION OF TEACHER CERTIFICATION PROGRAM: AN EVALUATION - Azhar, Fadly; Erni; Dahnilsyah (Prodi Administrasi Pendidikan Program Pascasarjana Universitas Riau, 2020)
This research aimed at evaluating the profile of teachers after the implementation of the certification program within the periods of 2006– 2015. The sample of this research was 367 teachers in Riau Province-Indonesia. Since this research evaluated input, process, and inhibiting factors in conducting pedagogy, professional, and the combination of pedagogy & professional competencies; the Context, Input, Process, and Product (CIPP) evaluation model was used. The research findings revealed that in the input factor, the aspects of knowledge on technology, information & communication (2.8856) and materials, structure, concept, & professional mindset (2.9319) were at a moderate level. Meanwhile, in the process factor, the aspects of reflective action for the improvement of learning quality (2.7036); and use of technology, information, communication dealing with self improvement (2.8283) were also in moderate level; but in low level for the aspect of creativity in material development In case of inhibiting factors, teachers have problems with copying facilities of learning materials, test, & quiz (65.7%); compulsory teaching load per week (73.0%); activities of classroom and subject teachers working group (67.6%); the utilization of school operation fund (76.3%); the process of promotion (65.4%); appointed to have additional jobs (95.6%); certification fund (50.1%); school library (22.9%); workshop, training, upgrading for teachers (43.6%); and reduction of certification fund (31.6%). However, there was no significant difference in the factors of input and process viewed from the aspects of types of teachers, academic qualification, teaching experience, and gender.